2020
DOI: 10.4236/wjet.2020.84049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical Properties and Antioxidant Activity of Wheat-Red Kidney Bean Biscuits

Abstract: This research was aimed to study the physicochemical properties and antioxidant activity of biscuits fortified with red kidney bean (Phaseolus vulgaris) powder. Proximate compositions, total phenol content, antioxidant activity, and functional properties of red kidney bean (RKB) powder were studied before and after the incorporation of red kidney bean in the biscuits. The bean powder was mixed with wheat flour at a level of 0% as control, 10%, 20%, and 30% during dough preparation. Results revealed that RKB po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The obtained results are in contrast with the findings of Rui et al (2011) Concerning fat content in raw of the two varieties of kidneys bean, the percentage of fat was found to be fairly low 2.05 and 1.4 g/100g for white and red beans, respectively. These values matched with Roy et al (2020) who found that the crude fat content in beans was about 3.07%, the variation might due to the cultivar and environmental impacts of varied regions. The ash content was found to be 3.09 and 5.63 g/100g, which falls within the range of 4.25% to 5.09% as recorded for various bean varieties (Rui et al, 2011).…”
Section: Percentage Of Dry Mater(n = 3)supporting
confidence: 87%
“…The obtained results are in contrast with the findings of Rui et al (2011) Concerning fat content in raw of the two varieties of kidneys bean, the percentage of fat was found to be fairly low 2.05 and 1.4 g/100g for white and red beans, respectively. These values matched with Roy et al (2020) who found that the crude fat content in beans was about 3.07%, the variation might due to the cultivar and environmental impacts of varied regions. The ash content was found to be 3.09 and 5.63 g/100g, which falls within the range of 4.25% to 5.09% as recorded for various bean varieties (Rui et al, 2011).…”
Section: Percentage Of Dry Mater(n = 3)supporting
confidence: 87%